Death - Scarre, Geoffrey (Central problems of philosophy., 2014)
What is death and why does it matter to us? How should the knowledge of our finitude affect the living of our lives and what are the virtues suitable to mortal beings? Does death destroy the meaningfulness of lives, or would lives that never ended be eternally and absurdly tedious? Can death really be an evil if, after death, we no longer exist as subjects of goods or evils? How should we respond to the deaths of others and do we have any duties towards the dead? These, and many other, questions are addressed in Geoffrey Scarre#x92;s book, which draws upon a wide variety of philosophical and literary sources to offer an up-to-date and highly readable study of some of the major ethical and metaphysical riddles concerning death and dying. Scarre shows that far from being a morbid subject for a philosophy book reflecting on death and its significance doubles as an illuminating way of reflecting on life.